Condoning the Use of Force: The UN Security Council as Interpreter of the Jus ad Bellum. (18th June 2018) - Johnstone, Ian
Abstract : Monica Hakimi's article probes the legal significance of an interesting phenomenon: the UN Security Council condoning the use of force, as opposed to authorizing it. She offers an innovative perspective on this little-studied dimension of how the Council contributes to the development of jus ad bellum . While I applaud much in the article, I question her characterization of what the Council is condoning in the cases she reviews. She claims these are "fact-specific decisions, " whereas I argue that the Council is endorsing controversial interpretations of the law on the use of force. This disagreement does not detract from Hakimi's observations about the policy implications of the practice, or about the Council's role as a site for deliberation and argumentation about the content of international law. But it does cast doubt on her conceptual claim that there are two distinct "regulatory forms, " which together provide the content of jus ad bellum, one particularistic and procedural, the other general and substantive. All legal claims and justifications entail the application of general standards to particular facts, either explicitly or implicitly. Most of her case studies can be explained in those terms. Thus, while the Council's practice of condoning the use of force is important to understand, the "conventional account" she derides provides a more persuasive and parsimonious explanation of that phenomenon.